Šamanizem na Slovenskem? Dileme o pojmih in pojavih šamanizma, obsedenosti in ekstaze Shamanism on Slovenian Territory? Dilemmas Concerning the Phenomena of Shamanism, Spirit Possession and Ecstasy - Šmitek, Zmago (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Are there elements of shamanism in Slovenian folklore tradition, or is it more adequate to use terms like spirit possession or ecstasy? The author’s conclusion, which is based Slovenian data and on comparative literature, is that it is difficult to differentiate these terms in practice. He also explains the possible original meaning of the names kresnik and vedomec.